2020
DOI: 10.1128/mra.00827-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Naganishia liquefaciens Strain N6, Isolated from the Japan Trench

Abstract: The draft genome sequence of the deep-sea yeast Naganishia liquefaciens strain N6, isolated from the Japan Trench, is reported here. This strain was previously classified into a Cryptococcus clade. Phylogenetic analysis using the presented sequence suggests that strain N6 is in the clade of the genus Naganishia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Close relatives of Vishniacozyma carnescens, i.e., V. alagoana and V. victoriae, were recently reported as endophytes of bromeliads (Félix et al, 2020) and maple tree (Wemheuer et al, 2019), respectively. In addition, some of the yeasts isolated in this study (Tausonia pullulans and Naganishia liquefaciens) were not reported earlier as endophytic colonizers in plants; however, their existence in soils and extreme habitats has been reported (Han et al, 2020;Li A. H. et al, 2020).…”
Section: Microbial Communities In a Euchromacontrasting
confidence: 48%
“…Close relatives of Vishniacozyma carnescens, i.e., V. alagoana and V. victoriae, were recently reported as endophytes of bromeliads (Félix et al, 2020) and maple tree (Wemheuer et al, 2019), respectively. In addition, some of the yeasts isolated in this study (Tausonia pullulans and Naganishia liquefaciens) were not reported earlier as endophytic colonizers in plants; however, their existence in soils and extreme habitats has been reported (Han et al, 2020;Li A. H. et al, 2020).…”
Section: Microbial Communities In a Euchromacontrasting
confidence: 48%
“…S6b), and the ability to thrive under conditions that are practically the same as those for S. cerevisiae, are highly advantageous traits as a model organism. Furthermore, we recently determined the draft genome sequence of this organism (Han et al 2020). Together, this has enabled the application of molecular genetics approaches to N. liquefaciens, which provide further means to promote in-depth study of Basidiomycota biology.…”
Section: Discussionmentioning
confidence: 99%
“…We recently drafted the whole genome sequence and gene structure of the strain N6 and used the obtained genomic data to construct a maximum-likelihood phylogenetic tree in the class Tremellomycetes (Han et al 2020). While the genome annotation is ongoing, this result further supported the classification of strain N6 within the clade of the genus Naganishia, leading us to propose that this strain be named Naganishia liquefaciens N6 (Han et al 2020). We do not currently have information about the ploidy or sexual cycle of this strain.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations